2006
DOI: 10.1097/01.mop.0000193291.09894.6c
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled nitric oxide therapy in premature newborns

Abstract: Trials of inhaled nitric oxide in premature newborns have yielded conflicting results to date, and the role of inhaled nitric oxide therapy in this population remains controversial. The largest trials of inhaled nitric oxide therapy in premature newborns have completed enrollment but have yet to be published. The results of these ongoing trials will help clarify the potential risks and benefits of inhaled nitric oxide therapy in the premature newborn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Breathing low concentrations of NO gas reduces pulmonary arterial pressures without producing systemic hypotension in animal models and children [ 14 , 15 ], and inhaled NO has been safely used to treat persistent pulmonary hypertension and other pulmonary disorders [ 16 , 17 ] in neonates and infants for over 20 years [ 18 ]. In Plasmodium berghei ANKA (PbA)-infected mice (a murine CM model), breathing 40 or 80 parts per million (ppm) of inhaled NO [ 19 , 20 ] improved survival rates, reduced plasma inflammatory markers, and increased plasma Ang-1 levels.…”
mentioning
confidence: 99%
“…Breathing low concentrations of NO gas reduces pulmonary arterial pressures without producing systemic hypotension in animal models and children [ 14 , 15 ], and inhaled NO has been safely used to treat persistent pulmonary hypertension and other pulmonary disorders [ 16 , 17 ] in neonates and infants for over 20 years [ 18 ]. In Plasmodium berghei ANKA (PbA)-infected mice (a murine CM model), breathing 40 or 80 parts per million (ppm) of inhaled NO [ 19 , 20 ] improved survival rates, reduced plasma inflammatory markers, and increased plasma Ang-1 levels.…”
mentioning
confidence: 99%
“…Although studies in newborns and infants suggest that inhaled NO is safe [32,33], the long-term pulmonary and extrapulmonary effects of inhaled NO are unknown. In particular, the effects of chronic NO inhalation on normal pulmonary cell proliferation and differentiation, as well as on alveolar and microvascular development, are unknown.…”
Section: Safety Of Inhaled No In the Newbornmentioning
confidence: 98%
“…Although long-term inhaled NO treatment has been used in the BPD patients, especially those who require continuous mechanical ventilation, no study has reported such data to date. Preventive low-dose inhaled NO supply can reduce the incidence of BPD in the preterm infants with birth weight greater than 1,000 g, but it showed no effect in the infants with birth weight less than 1,000 g. Therefore, the use of preventive inhaled NO for BPD prevention is questionable30, 31). Most patients require an initial inhaled NO dose of 10-20 parts per million (ppm) for PH treatment and a maintenance dose of 2-10 ppm for weaning.…”
Section: Treatment Of Ph In the Bpd Patientsmentioning
confidence: 99%